(untitled) (KIUT Publication, 2025)
The article analyzes the architecture of old quarters of historical cities of Turkey, and in particular the interior decoration of houses. The formation of quarters, life of quarters, external and internal appearance of houses, architectural elements, the relationship of cultural values are studied. The results of the study are considered an important experiment for ideas on preserving old urban areas and adapting them to modern development.